2020
DOI: 10.7554/elife.55092
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological marker of arousal level in humans

Abstract: Deep non-rapid eye movement sleep (NREM) and general anesthesia with propofol are prominent states of reduced arousal linked to the occurrence of synchronized oscillations in the electroencephalogram (EEG). Although rapid eye movement (REM) sleep is also associated with diminished arousal levels, it is characterized by a desynchronized, ‘wake-like’ EEG. This observation implies that reduced arousal states are not necessarily only defined by synchronous oscillatory activity. Using intracranial and surface EEG r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

40
352
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(395 citation statements)
references
References 93 publications
40
352
3
Order By: Relevance
“…As a consequence, the spectral profiles are inherently statistical in nature. In coherence with former reports focusing on sleep stages and arousal 15 , 16 our current approach provides a characterization of the NREM sleep EEG Fourier spectra by taking into account their inherent electrophysiological and statistical regularities based on its power law scaling properties. Our focus is on individual differences in NREM sleep and we assume that the approach we follow results in an integrated characterization of NREM sleep EEG, which is superior in terms of construct validity and accuracy.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…As a consequence, the spectral profiles are inherently statistical in nature. In coherence with former reports focusing on sleep stages and arousal 15 , 16 our current approach provides a characterization of the NREM sleep EEG Fourier spectra by taking into account their inherent electrophysiological and statistical regularities based on its power law scaling properties. Our focus is on individual differences in NREM sleep and we assume that the approach we follow results in an integrated characterization of NREM sleep EEG, which is superior in terms of construct validity and accuracy.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to the spectral intercepts, the power law functions describing the sleep EEG spectra appropriately address the issue of the ratio of EEG power at different frequencies, providing a single measure ( α ), instead of several ones scattered redundantly in all frequency bins and bands. This approach was found to be effective in deriving measures of consciousness 24 , sleep stages 15 and arousal 16 from sleep EEG records, as well as to index aging as a function of scale free wake EEG features 22 . Here we complete these studies with the individual differences approach of NREM sleep EEG, which was suggested to be a seminal perspective of all sleep studies 45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A vast body of literature has demonstrated the existence of several oscillatory frequency bands, ranging from approximately 0.05 Hz to 150 Hz (up to 500 Hz in animals) 4 that have been associated with a diversity of complex cognitive operations. Furthermore, these narrowband oscillations, commonly referred to as delta (1-4 Hz), theta (4-8 Hz), alpha (8)(9)(10)(11)(12), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma (> 30 Hz) 5 , have widely been studied during resting-state settings to better understand network dynamics. Multiple studies have also been employed in patient populations 6,7 as resting-state narrowband oscillations have been shown to correlate with cognitive functions 8,9 .…”
mentioning
confidence: 99%